ADRM1 as a therapeutic target in hepatocellular carcinoma. Issue 1 (11th September 2020) - Liang, Yu‐Cen; Wang, Ji‐Lin; Wang, Hong‐Tao; Liu, Hu; Zhang, Hong‐Long; Liang, Yu‐Xia
Abstract: Hepatocellular carcinoma (HCC), a primary liver tumor, is the third leading cause of cancer‐related mortality worldwide. The proteasome system is overactivated in the majority of tumors, including HCC. However, targeting the proteasome system in HCC is not as effective as in other types of cancer. Therefore, a new target of HCC therapy needs to be identified, and the potential mechanism must be studied. Using the The Cancer Gene Genome Atlas and GEO datasets, the present investigation demonstrated for the first time that ADRM1 is overexpressed in HCC, and the high level of its expression predicts poor overall survival in HCC patients. The high expression of ADRM1 in HCC was verified using tumor tissue arrays. By comparing paired tumor and nontumor tissues, it was shown that the majority of HCC patients (76.25%) exhibited higher ADRM1 expression in the tumor than in normal tissues. in vitro experiments demonstrated that targeting ADRM1 with shRNAs significantly suppressed the proliferation of HCC cells. RA190, a specific inhibitor of ADRM1, suppressed cell proliferation and colony formation by HCC cells in a concentration‐dependent manner. The study of the mechanism of the effects of RA190 revealed that targeting ADRM1 blocked the G2/M transition in the cell cycle and induced apoptosis of HCC cells. Together, the obtained results indicate that ADRM1 is a promising target for HCC therapy and suggest that ADRM1 inhibitors, such as RA190, have the potential for clinical application in the treatment of HCC.